Sertifikasi Halal Produk Makanan Olahan Ketela oleh UMKM Desa Krebengan Berbasis Kewajiban Peraturan Hukum Positif - Wiwin Muchtar Wiyono; Aris Priyadi; Teguh Anindito (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study aims to analyze the understanding of halal certification among UMKM cassava product actors in Kebrengan Village. This study was conducted using a sociological juridical approach method and was conducted using a qualitative descriptive approach. Data collection was carried out by interviews and documentation of related sources. Respondents were 26 people. The results of this study show that the understanding of halal certification in Kebrengan Village, Mojotengah District, Wonosobo Regency is still relatively low due to the lack of understanding and socialization activities. The role of the government is needed to improve the understanding of UMKM by organizing socialization activities and assistance to facilitate obtaining halal certification in Kebrengan Village